2014
DOI: 10.1049/iet-net.2013.0005
|View full text |Cite
|
Sign up to set email alerts
|

Approach for channel reservation and allocation to improve quality of service in vehicular communications

Abstract: Channel allocation plays an important role in next generation of wireless networks that require huge bandwidth support for various applications. It became very interesting and important research area in vehicular ad hoc network (VANET) as the channel allocation procedure needs to be efficient as the frequency of handoff is high because of the high mobility of the nodes. So, the authors propose a channel allocation algorithm that utilises channel reuse technique, channel borrowing process and the speed of the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…There has been a great body of research on CAC design reported in the literature [1,5,6,[12][13][14][15][16][17][18]. In this section, we highlight a few important papers that mainly focus on reservation-based schemes in cellular and vehicular networks.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…There has been a great body of research on CAC design reported in the literature [1,5,6,[12][13][14][15][16][17][18]. In this section, we highlight a few important papers that mainly focus on reservation-based schemes in cellular and vehicular networks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The CAC design for vehicular networks is discussed in [5,15,16], where the vehicular environment and movement has a major impact on the system design. Hence, the macroscopic vehicular modeling (CMVM) was introduced in CAC design in [5] where the macroscopic modeling describes vehicular traffic with aggregate variables such as traffic density, mean speed, etc.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…[3][4][5]), wireless (e.g. [6][7][8]) and optical networks (e.g. [9,10]) show the importance of the policy in teletraffic engineering.…”
Section: Introductionmentioning
confidence: 99%